(untitled) (Revista científica Olimpia, 2020)
The sports performance of the athletes and his incidence in his teams’ result has been gone into from several disciplines. In present it contributions documented in entrepreneurial contexts to create matrix of competitive profile for teams of soccer took investigation like reference and that way evaluating the national team’s athletes Cuban of category of the female sex, that took part in the Tournament of Development of the Caribe in Trinidad And Tobago in October 2019. The assessment of the soccer players according to his position: Janitress, center halfbacks, lateral defenses, fliers of argument, fliers of creation, extremes or foremost center and the their evaluation of the status out of every one allowed the team’s director taking more rational decisions in the pre-competitive and competitive stages.